Automated Latex Agglutination and ELISA Testing Yield Equivalent D-Dimer Results in Patients with Recent Myocardial Infarction - for the THROMBO Research Investigators; Marder, Victor J.; Zareba, Wojciech; Horan, John T.; Moss, Arthur J.; Kanouse, Joel J. (Thrombosis and Haemostasis, 1999)
Our previous prospective study of post-infarction patients described a strong and significant association of increased plasma D-dimer concentrations in those who experienced a subsequent coronary death or non-fatal myocardial infarction. In the present study, we compare results on stored plasma obtained two months after the index myocardial infarction from 1,038 patients of this trial, using a simple automated latex agglutination (LA) assay in parallel with the standard ELISA test. Results show a somewhat higher mean value for the LA assay (702 ± 1092 vs. 638 ± 986 ng/ml, p = 0.0002), a strong linear correlation of the two assays (r = 0.86) and 88% agreement for values below 500 ng/ml by the ELISA test. D-dimer concentrations determined by each assay were highly correlated in patients with subsequent coronary artery events (p = 0.93) and quartile values for both the LA and ELISA were equally predictive of such events (p = 0.003 and p = 0.001, respectively). This is the first demonstration that a latex agglutination assay for D-dimer can be used to assess the prognostic risk of recurrent coronary thrombotic disease after myocardial infarction